Smart manufacturing : digital twin - Tan, Peng Yu (2019)
Smart Manufacturing – Digital Twin is initiated to aid in digitalization of an entire shop floor, with focus on the manufacturing cell. With a physical setup prepared, the goal is to mimic the entire production process, including machines and parameters. With the digital twin, a secondary objective is to enable optimization of processes in the virtual environment. The software provided for Digital Twin will be 3DEXPERIENCE, a business experience platform suited for engineering organizations. 3DEXPERIENCE provides value-adding solutions from marketing to sales to engineering, promoting collaboration and seamless connectivity. The main solutions from 3DEXPERIENCE for this project will be focused on CATIA to provide the engineering design tools to recreate the mold for injection molding, SIMULIA to provide simulation tools in plastic injection molding and DELMIA to provide planning, programming and simulating of virtual twin. The author manages to model the mold and CNC machine using CATIA but dimensions and parameters are not actual values due to lack of resources. Simulations of the plastic injection flow are performed using SIMULIA and two comparisons are discussed, along with the author’s deduction. A tooling path is programmed and simulated using DELMIA to demonstrate how the CNC tooling head will travel. The end result of this project is a Digital Twin but without sufficient depth and accuracy. The reasoning behind was due to time constraint, immense work required and lack of knowledge on both software and manufacturing field.